O impacto da usabilidade na aprendizagem por meio de jogos educacionais digitais - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Educational games can be designed to promote learning about a certain content. Learning is a unique personal interpretation of each person and is consolidated through their own experiences. There is a possibility of these experiences be acquired through digital educational games. The problem that presents itself is summed up in one question: is there a relation between the usability of digital educational games and learning through content? This course conclusion work aims to conduct a study on the impact of usability in learning through digital educational games proposing and developing an educational game in two versions. Compare student learning after playing these games and present evidence of a relationship between the usability of the games and the learning of its contents, beyond contributing to the development of digital educational games. The results of this relationship were obtained through a questionnaire administered as a pre-test, immediate post-test and post-test performed three days after the game session. From these tests is made an average of correct questions for those who played the game with high and low usability. In the final results, we did not observe a significant difference between the performances of the participants. The learning ability was higher in the game with high usability in the immediate pre-test, but there was a higher forgetting who played the game with high usability in the post-test carried out three days later.
Keywords: Software Engineering; Educational Games; Usability; Learning; Engenharia de software; Jogos Educacionais; Usabilidade; Aprendizagem; CNPQ::CIENCIAS EXATAS E DA TERRA